THE RELATIONSHIP OF OUTSIDE HOUSE ACTIVITIES AT NIGHT AND THE USE OF NETS WITH THE EVENT OF MALARIA IN SIBOLGA UTARA DISTRICT YEAR 2021 - Asrina Sitompul; Ayu Muzda; Putri Intan (Science Midwifery, 2021)
Malaria is an infectious disease that is still an important problem in Indonesia, especially in achieving the goal of a Malaria-free Indonesia in 2030 through the program to eradicate malaria again. The prevalence of malaria in Indonesia is still quite high, 2.9% of the total population of Indonesia. Meanwhile in Riau Islands Province, the prevalence is 1.4% and in Batam City 1.1%. The existence of breeding places in the form of water puddles ex-sand excavations, lakes, sewers that do not flow, ponds that are not maintained, which are widely available in Batam are supporters of malaria. The habit of residents doing activities outside the house at night and selfprotection by using speech nets affects the incidence of malaria in Batam City. This study aims to determine the relationship between activities outside the house at night to the incidence of malaria and the relationship between the use of mosquito nets to the incidence of malaria that occurred in the district of South Sibolga and its impact on the community. This study used a case-control design, where cases were malaria sufferers found during a mass blood survey, and controls were taken from the same activity. The risk factor data used primary data obtained from interviews with case and control respondents. From the results of the study, it was found that respondents who did activities outside the house at night were at risk of suffering from malaria by 2.6 times (ORcrude = 1.623; ORadjusted = 2.578) compared to respondents who did not go out of the house at night after being controlled by the variables of age, gender. , use of mosquito nets and use of mosquito repellent. The impact caused by activities outside the house at night in the population is 29%. Meanwhile, respondents who do not use mosquito nets at night are at risk of suffering from malaria by 2.3 times compared to those who use mosquito nets (ORcrude = 1,629; ORadjusted = 2,313) after being controlled by the variable length of stay, activities outside the house at night and the use of mosquito repellent. The impact on the population is 47%. To reduce the incidence of malaria, it is necessary to increase the coverage of the use of mosquito nets by distributing insecticide-treated mosquito nets, counseling on the use of long-sleeved clothes and topical mosquito repellent when outside the home.